2014
DOI: 10.1177/1362168814541717
|View full text |Cite
|
Sign up to set email alerts
|

Task-modality and L1 use in EFL oral interaction

Abstract: This study examines whether task-modality (speaking vs. speaking+writing) influences first language (L1) use in task-based English as a foreign language (EFL) learner–learner interaction. Research on the topic has shown that different task-modality triggers different learning opportunities with collaborative speaking tasks drawing learners’ attention to meaning and tasks that also incorporate a written component drawing attention more to formal linguistic aspects. Research has also shown that a balanced L1 use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
79
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 50 publications
(103 reference statements)
12
79
3
Order By: Relevance
“…In line with our hypothesis, and previous studies focusing on L1 use by adults (Azkarai & García Mayo, 2015;Storch & Aldosari, 2010;Swain & Lapkin, 2000), these children Notes. ETR = exact task repetition; PTR = procedural task repetition.…”
Section: Main Findings On Luse and Functions In Young Efl Learnerssupporting
confidence: 91%
See 4 more Smart Citations
“…In line with our hypothesis, and previous studies focusing on L1 use by adults (Azkarai & García Mayo, 2015;Storch & Aldosari, 2010;Swain & Lapkin, 2000), these children Notes. ETR = exact task repetition; PTR = procedural task repetition.…”
Section: Main Findings On Luse and Functions In Young Efl Learnerssupporting
confidence: 91%
“…These studies have shown that, overall, EFL learners do not make an excessive use of their L1 (under 20% in García Mayo, 2015, andin Storch &Aldosari, 2010). With regard to the functions the L1 serves, research in EFL settings has shown that learners employ their L1 mainly with a metacognitive function, for metatalk, phatics -expressions such as 'mmm, yeah, ok' -and for vocabulary searches, although these functions might vary depending on the task that learners are carrying out (see Alegría de la Colina & García Mayo, 2009;Azkarai & García Mayo, 2015;Storch & Aldosari, 2010). The different functions the L1 serves help learners clarify different aspects of task procedure, keep interest in the task and formulate their goals (Alley, 2005;Antón & DiCamilla, 1998;Brooks & Donato, 1994).…”
Section: L1 Use In Task-based Interactionmentioning
confidence: 98%
See 3 more Smart Citations